Chemical composition and in vitro chemoprevention assessment of Eugenia jambolana Lam. (Myrtaceae) fruits and leaves - Dametto, Alessandra C. [UNESP]; Agustoni, Daniele [UNESP]; Moreira, Thais F. [UNESP]; Plaza, Carenina V. [UNESP]; Prieto, Aline M. [UNESP]; Silva, Tarsia G.A. [UNESP]; Souza, Felipe O. [UNESP]; Boralle, Nivaldo [UNESP]; Maria Sorbo, Juliana [UNESP]; Silva, Dulce H.S. [UNESP]; Soares, Christiane P. [UNESP] (Elsevier, 2017)
Eugenia jambolana has been used as an antioxidant, anti-inflammatory and antidiabetic. This study performed a chemical and chemopreventive screening of extracts and fractions from leaves and fruits from Eugenia jambolana. The purification of the crude extract from leaves afforded two known flavonoids, tricetin-4′-O-α-L-rhamnopyranoside (1), and myricitrin (2), whereas the purification of crude extract from fruits afforded one anthocyanin, malvidin-3-O-gentibioside (3). Additionally, seven anthocyanins were tentatively identified. The antigenotoxicity results showed that post-treatment with extracts and fractions mitigated the damage induced by hydrogen peroxide. In assessing the antimutagenicity, the samples were able to reduce the frequency of micronucleus formation for both pre-treatment and post-treatment. Also, extracts and fractions promoted the induction of quinone reductase activity. Such extracts and fractions were able to induce detoxifying enzymes and reverse DNA damage, an essential balance for its applicability as a chemopreventive agent.
Keywords: Anthocyanins; Antigenotoxicity; Chemoprevention; Eugenia jambolana; Flavonoids